Prevalence of Masked Hypertension in African Americans. Issue 11 (20th October 2014) - Larsen, Timothy R.; Gelaye, Alehegn; Waanbah, Barryton; Assad, Hadeel; Daloul, Yara; Williams, Frances; Williams, Michael; Steigerwalt, Susan
<x xml:space="preserve">Abstract</x> Masked hypertension (MH), the presence of normal office blood pressure (BP) with elevated ambulatory pressure, has been shown to correlate with organ damage. Population‐based studies from Europe and Asia estimate a prevalence of 8.5% to 15.8%. Two small studies in African Americans estimate a prevalence >40%. Therefore, the authors utilized ambulatory BP monitoring (ABPM) to identify the prevalence of MH in our African American population. Pressure was recorded every 30 minutes while awake and every 60 minutes while asleep. Patients with 24‐hour average BP ≥135/85 mm Hg, awake average BP ≥140/90 mm Hg, or asleep average BP ≥125/75 mm Hg had MH. Seventy‐three participates had valid data. The mean age of the patients was 49.8 years, mean body mass index was 31.1, and 39 patients (53%) were women. Thirty‐three patients (45.2%) had MH. Patients with MH had higher clinic systolic BP and trended toward higher BMI values. The authors corroborated the high prevalence of MH in African Americans. ABPM is critical to diagnose hypertension in African Americans, particularly in those with high‐normal clinic pressure and obesity.